Spatial patterns of grasses influence soil macrofauna biodiversity in Amazonian pastures - Mathieu, J.; Grimaldi, Michael; Jouquet, Pascal; Rouland, C.; Lavelle, Patrick M.; Desjardins, Thierry; Rossi, J.P. (Elsevier, 2009)
Grasslands are often characterized by small-scale spatial eterogeneity due to the juxtaposition of grass tufts and bare ground. Although the mechanisms generating plant spatial patterns have been widely studied, few studies concentrated on the consequences of these patterns on belowground macrofauna. Our objective was to analyze the impact of grass tuft (Brachiaria bryzantha cv. marandu) spatial distribution on soil macrofauna diversity in Amazonian pastures, at a small scale (less than 9 m2). Soil macrofauna was sampled among B. bryzantha tufts, which showed a variable spatial distribution ranging from dense to loose vegetation cover. The vegetation configuration explained 69% of the variation in total soil macrofauna density and 68% of the variation in total species richness. Soil macrofauna was mainly found in the upper 10 cm of soil and biodiversity decreased with increasing distances to the nearest grass tuft and increased with increasing vegetation cover. The size of the largest grass tuft and the microlandscape connectivity also had a significant effect on biodiversity. The density and species richness of the three principal soil ecological engineers (earthworms, ants and termites) showed the best correlations with vegetation configuration. In addition, soil temperature significantly decreased near the plants, while soil water content was not influenced by the grass tufts. We conclude that soil macrofauna diversity is low in pastures except close to the grass tufts, which can thus be considered as biodiversity hotspots. The spatial arrangement of B. bryzantha tussocks influences soil macrofauna biodiversity by modifying soil properties in their vicinity. The possible mechanisms by which these plants could affect soil macrofauna are discussed.